Current calcium fortification experiences: a review. Issue 1 (18th September 2020) - Palacios, Cristina; Hofmeyr, G. Justus; Cormick, Gabriela; Garcia‐Casal, Maria Nieves; Peña‐Rosas, Juan Pablo; Betrán, Ana Pilar
Abstract: Low dietary calcium is very common in many populations, contributing to nutritional rickets/osteomalacia in children/adults and increasing the risk of several health problems. Calcium is a nutrient of concern as the recommended nutrient requirements are difficult to meet in the absence of dairy products. The provision of culturally acceptable calcium‐fortified foods may improve calcium intake when it is a feasible and cost‐effective strategy in a particular setting. This landscape review was conducted in 2019 and describes current calcium fortification efforts and lessons learned from these experiences. Worldwide, the United Kingdom is the only country where calcium fortification of wheat flour is mandatory. It is estimated that this fortified staple ingredient contributes to 13–14% of calcium intake of the British population. Other items voluntary fortified with calcium include maize flour, rice, and water. Current calcium fortification programs may lack qualified personnel/training, clear guidelines on implementation, regulation, monitoring/evaluation, and functional indicators. Also, the cost of calcium premix is high and the target groups may be hard to reach. There is a lack of rigorous evaluation, particularly in settings with multiple micronutrient programs implemented simultaneously, with low quality of the evidence. Further research is needed to assess the impact of calcium fortification programs.